Obtención y caracterización de carboximetil celulosa (cmc) a partir de los forrajes pasto elefante (pennisetum sp) y king grass (pennisetum hybridum) para su aplicación en la industria alimentaria. - Cazco Barba, Carmen Antonieta (2017)
Forages have cellulose in their structure with food and non-food. applications This study seeks to obtain and characterize carboxymethyl cellulose (CMC) where the response surface methodology was used to optimize cellulose production in leaves of elephant grass, Green King Grass and Purple King Grasss, using sodium hydroxide (NaOH) as an insulator and ethylenediaminetetraacetic acid ( EDTA) as a chelating agent to minimize ash. The independent variables were% NaOH and% EDTA, with two continuous parameters, the temperature of (80-90 ° C) and time (120 min). The dependent variables were cellulose yield, ash content and α-cellulose content. Optimum conditions were defined by: 25% NaOH concentration, 10% EDTA concentration. The cellulose yield was 34.91%, α-cellulose content 80.15%, and ash content 2.20%. To obtain CMC , % NaOH and weight of Monochloroacetic Acid (MCA) were studied as independent variables. The dependent variables were CMC yield, degree of substitution and degree of purity, applying the same principle of response surface conditions were: 50% NaOH, 2g of MCA. The CMC of Green King Grass was better results, with a final yield of 1.89 g/g, 0.77 degrees of substitution, degree of purification of 95.39% and 40.73 mPas. Concluding that CMC can be obtained from forages.